Transformacja gospodarcza w krajach Europy Środkowo-Wschodniej a handel zagraniczny tych państw - Stawicka, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
At the turn of the 80s and 90s, the authorities of Central-Eastern European countries made a decision of releasing from political system, in which, since ages, they had functioned, and came into system of free economy. This fact launched economy transformation in these countries. The transformation process from a centrally planned economy to a free market economy started at the beginning of 90s. Poland was the first country which made this effort in 1989, followed in the next years by Hungary, the Czech Republic and Slovakia and other countries. At the latest, this process was launched in the countries of former Union of Soviet Socialist Republics after they gained independence from the Soviet Union. Most of today's Central-Eastern European countries are economies widely open for exchange with foreign countries and they are heavily dependent on export, import and inflow of foreign direct investments. It results not only from natural and economic conditions but also from progress in trade liberalization and international co-operation. Nearly in all Central-Eastern European countries the need for transformation of political system into direction of capitalism was of populist implied meaning. Average inhabitant of social country headed for wealth but not in every country it was possible to approach. However, these countries have latent economic potential and ideal geographical localization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 628-638